IFAS's IPM, BMPs, FYN and More: An Alphabet Soup of Good Environmental Programs for Florida - D. J. Sonke; Norman C. Leppla (EDIS)
The University of Florida Institute of Food and Agricultural Sciences (IFAS) has three related programs that often are confused within the IFAS community and by our clientele: Integrated Pest Management (IPM), Best Management Practices (BMPs), and Florida Yards and Neighborhoods (FYN). This document is ENY-704, one of a series of the Department of Entomology and Nematology, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: November 2004.